Pengaruh Ekstrak Daun Senduduk Bulu (Clidemia hirta L.) terhadap Perkecambahan dan Pertumbuhan Gulma (Praxelis clematidea) - Andriani Dwi Lestari; Hidayat Pujisiswanto; Herry Susanto; Nanik Sriyani (JURNAL AGROTROPIKA, 2023)
Weeds are plants whose existence is not expected by farmers because they interfere with cultivated plants. But there are weeds that can produce phenolic compounds such as Clidemia hirta L which can be used as bioherbicides. This study aims to determine the effect of Clidemia hirta L. leaf extract on the germination and growth of Praxelis clematidea weeds. The research was carried out from June 2021 to September 2021 at the Weed Science Laboratory and Integrated Field Laboratory, Faculty of Agriculture, University of Lampung. This study used a completely randomized design (CRD) method with 6 treatments with concentrations of Clidemia hirta L leaf extract, namely 0; 1.5; 3.0; 4.5; 6.0; and 7.5%. Each treatment was repeated 6 times to obtain 72 experimental units. The observed variables are germination, crown height, root length, dry weight, and weed poisoning level. The data obtained were analyzed by analysis of variance and continued with the Least Significant Difference Test (LSD) at the 5% level. The results showed that the germination of Praxelis clematidea weed was significantly inhibited by the treatment of Clidemia hirta L leaf extract with a concentration of 1.5; 3.0; 4.5; 6.0; and 7.5%. While concentrations of 3.0%, 4.5%, 6.0%, and 7.5% Clidemia hirta L. leaf extract  inhibited the growth of Praxelis clematidea weeds in the greenhouse. Key words:  Clidemia hirta L., extract, Praxelis clematidea, germination, growth